2022
DOI: 10.34117/bjdv8n4-052
|View full text |Cite
|
Sign up to set email alerts
|

Iogurte artesanal enriquecido com polpa de cupuaçu e semente de linhaça dourada / Artisanal yoghurt enriched with cupuaçu pulp and golden flaxseed

Abstract: Buscou-se desenvolver um iogurte artesanal enriquecido com diferentes concentrações de polpa de cupuaçu e semente de linhaça dourada, resultando em um produto com alto valor agregado comercial, nutritivo e funcional, valorizando sobretudo o cupuaçu, por ser um fruto amazônico típico da região Norte, e que está inserido na cultura alimentar local. Três formulações de iogurte, foram elaborados. Realizou-se análises de composição centesimal e físico químicas, além de análises microbiológicas de coliformes totais,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Similar results were not observed bySanto et al (2012) andSenadeera et al (2018), whose control yogurts showed lower total acidity values than those added with fruit extracts of passion fruit and anona, respectively.The results on the composition of the formulations indicate that the treatments with the addition of PPP influenced the protein and fat contents. Differences in the protein and fat content of yogurt may result from the raw material and ingredients used and/or be related to the proteolytic and lipolytic activity of the microorganisms, data evidenced byShori et al (2022), who observed higher protein values in yogurts with the addition of vegetable extracts, andLopes et al (2022), who identified more elevated levels of protein, fat and ash in cupuaçu and golden flaxseed yogurt.…”
mentioning
confidence: 99%
“…Similar results were not observed bySanto et al (2012) andSenadeera et al (2018), whose control yogurts showed lower total acidity values than those added with fruit extracts of passion fruit and anona, respectively.The results on the composition of the formulations indicate that the treatments with the addition of PPP influenced the protein and fat contents. Differences in the protein and fat content of yogurt may result from the raw material and ingredients used and/or be related to the proteolytic and lipolytic activity of the microorganisms, data evidenced byShori et al (2022), who observed higher protein values in yogurts with the addition of vegetable extracts, andLopes et al (2022), who identified more elevated levels of protein, fat and ash in cupuaçu and golden flaxseed yogurt.…”
mentioning
confidence: 99%